2013
DOI: 10.5251/abjna.2013.4.3.227.233
|View full text |Cite
|
Sign up to set email alerts
|

Water transmission properties of a sandy loam soil under different tillage practices in Maiduguri, Nigeria.

Abstract: Knowledge of water transmission properties of soils could play a significant role in the choice of appropriate water management practices capable of alleviating production constraints of predominantly coarse textured soils of semi arid environments. The effect of 3 tillage systems (no-till :NT, reduced-till: RT and conventional tillage: CT) on water transmission properties of a sandy loam soil in Maiduguri was investigated after 9-15 years of management. Within the growing season of 2010, saturated hydraulic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Consequently, the land cover type was later found to have a significant effect on Ksat. is phenomenon is not unusual because it is not unusual to obtain variation in Ksat depending on the depth and the method in use [88], type of soil, for example, sandy versus clayey soils [86], land use practice [89], type of vegetation, and landform [90].…”
Section: Soil Properties In Various Land Cover Types Soil Ph Is An Imentioning
confidence: 99%
“…Consequently, the land cover type was later found to have a significant effect on Ksat. is phenomenon is not unusual because it is not unusual to obtain variation in Ksat depending on the depth and the method in use [88], type of soil, for example, sandy versus clayey soils [86], land use practice [89], type of vegetation, and landform [90].…”
Section: Soil Properties In Various Land Cover Types Soil Ph Is An Imentioning
confidence: 99%
“…This suggested that the ability of soil water absorption was not only affected by the degree of soil water repellency as indicated by RI. The main reason is that RT treatment improved soil pore structure and water transmission (Gao et al, 2019;Li et al, 2021;Sauwa et al, 2013), which attenuated the effect of the increase in RI on soil water absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Moroke et al, (2009) also observed higher IR in DT than CT due to ample amount of macropores which led to the fast entry of water into the soil profile. The effect of tillage-residue management practices on cumulative infiltration (CI) is presented in Fig 2. After 300 minutes, maximum CI (cm) was observed under DT (33.1) followed by NTR (28.5), NT (23.0) might be due to relatively smaller pore heterogeneity and discontinuity of pores (Sauwa et al,. 2013).…”
Section: Resultsmentioning
confidence: 99%